2018
DOI: 10.1080/02640414.2018.1511318
|View full text |Cite
|
Sign up to set email alerts
|

Utility of international normative 20 m shuttle run values for identifying youth at increased cardiometabolic risk

Abstract: The purpose of this study was to examine the ability of international normative centiles for the 20 m shuttle run test (20mSRT) to identify youth at increased cardiometabolic risk. This was a cross-sectional study involving 961 children aged 10-17 years (53% girls) from the United Kingdom. Receiver operating characteristic (ROC) curves determined the discriminatory ability of cardiorespiratory fitness percentiles for predicting increased cardiometabolic risk. ROC analysis demonstrated a significant but poor di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 46 publications
(61 reference statements)
1
16
0
1
Order By: Relevance
“…From the structural equations carried out it can be seen that an increase in the perceived difficulty of physical education goes hand in hand with an increase in reports of its usefulness, coherence in the way it is managed and empathy towards the teacher who imparts it [87]. It can be confirmed that when each one of these variables increases, so to do the other variables, except in the case of coherence in subject management.…”
Section: Discussionmentioning
confidence: 92%
“…From the structural equations carried out it can be seen that an increase in the perceived difficulty of physical education goes hand in hand with an increase in reports of its usefulness, coherence in the way it is managed and empathy towards the teacher who imparts it [87]. It can be confirmed that when each one of these variables increases, so to do the other variables, except in the case of coherence in subject management.…”
Section: Discussionmentioning
confidence: 92%
“…More recently, there have been efforts to identify where a CRF cut-point falls within a normative-referenced distribution. Buchan et al (2019) developed 20-m shuttle-run test cut-points to identify youth living in the United Kingdom at increased cardiometabolic risk. The cut-points they identified were at the 60th percentile for males and the 55th percentile for females when using international normative-referenced centile values (Buchan et al 2019;Tomkinson et al 2017).…”
Section: Males Femalesmentioning
confidence: 99%
“…Buchan et al (2019) developed 20-m shuttle-run test cut-points to identify youth living in the United Kingdom at increased cardiometabolic risk. The cut-points they identified were at the 60th percentile for males and the 55th percentile for females when using international normative-referenced centile values (Buchan et al 2019;Tomkinson et al 2017). Using a slightly different approach, a study in Norwegian youth using directly measured V O 2peak testing identified CRF cut-points that fell within the 2nd, 5th, and 10th percentile for male and female children and youth to help identify those with 6, ≥5, and ≥4 cardiometabolic risk factors, respectively (Aadland et al 2019).…”
Section: Males Femalesmentioning
confidence: 99%
“…Falk and Dotan (56) have presented an excellent 2018 review of the topic but, as in 2017, the year 2018 witnessed a plethora of publications based not on rigorous assessment of peakVO 2 but on its estimation from field tests. Numerous publications have focused on either the development of variants of the 20-m shuttle run test (20mSRT) to estimate peakVO 2 (eg, 13,29,106) or the establishment of reference values for cardiometabolic risk in childhood based on peakVO 2 expressed in ratio with body mass (eg, 5,26,152). The 20mSRT has been proposed as a suitable and feasible health indicator for international surveillance in children and adolescents (90) and as a means of evaluating physical activity interventions (89).…”
Section: Commentarymentioning
confidence: 99%